Exploring employee perspectives of branding: a case study of Purple Wave Auction - Chumchal, Hannah (Kansas State University, 2024)
Purple Wave Auction, an auction house based in Manhattan, Kansas, has established itself as a trailblazer in the online equipment auction industry since its founding in 2000. Specializing in the direct selling of agricultural, construction, and fleet equipment through fully online, no-reserve auctions, Purple Wave Auction has earned a reputation for reliability and transparency. This paper proposes a case study analysis to probe Purple Wave Auction's employees, aiming to assess their impact on overall brand identity. By understanding how their branding is perceived by employees, Purple Wave Auction and other businesses can identify areas for improvement and strengthen their brand presence in the market amidst changing dynamics and stiff competition.
Keywords: Purple Wave Auction; Branding; Marketing; Brand identity; Brand strategy; Case study